2021
DOI: 10.1021/acsaelm.1c01028
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Triboelectric Nanogenerators Based on Chemical Modification of Conventional Textiles for Application in Electrically Driven Antibacterial Devices

Abstract: The energy harvesting provided by wearable triboelectric devices represents a promising procedure that circumvents typical drawbacks of conventional batteries in several applications. The development of wearable triboelectric generators with modified cotton in the presence of conductive and antibacterial agents can be considered an important step toward developing autonomous devices to be applied in electrically driven antibacterial treatments. The antibacterial properties of polypyrrole and its high conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The stress−strain profiles shown in Figure 3c confirm that mechanical properties of the chemically modified ESM@PPy proved a reinforcement in both tensile strength and elongation at the break with the incorporation of polypyrrole�while the maximum tensile strength for ESM is 3.2 MPa with an elongation of 10.2%, the direct polymerization of PPy on ESM returned the highest tensile (7.1 MPa) and elongation of 21.2%. 22,61 Kaynak et al 63 reported corresponding results for wool yarns coated with polypyrrole and attributed the increase in the elongation at break and tensile strength due to the modification in the surface morphology of the fibers under chemical polymerization. The results for the tensile strength of pristine ESM were close to those reported in ref 53, which obtained values in the order of 3.5 MPa for ESM treated with citric acid and acetic acid.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stress−strain profiles shown in Figure 3c confirm that mechanical properties of the chemically modified ESM@PPy proved a reinforcement in both tensile strength and elongation at the break with the incorporation of polypyrrole�while the maximum tensile strength for ESM is 3.2 MPa with an elongation of 10.2%, the direct polymerization of PPy on ESM returned the highest tensile (7.1 MPa) and elongation of 21.2%. 22,61 Kaynak et al 63 reported corresponding results for wool yarns coated with polypyrrole and attributed the increase in the elongation at break and tensile strength due to the modification in the surface morphology of the fibers under chemical polymerization. The results for the tensile strength of pristine ESM were close to those reported in ref 53, which obtained values in the order of 3.5 MPa for ESM treated with citric acid and acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the tensile strength of ESM coated by GNP and GNP + PPy had a slight variation, compared to the pure sample, with values of 3.4 and 3.3 MPa, and elongations of 14.9 and 10.7%, respectively. The lower values in tensile strength and elongation for GNP-based modified membranes are a consequence of a more complex modification coating process that involves successive drying steps at high temperatures for deposition of a thicker layer of GNP . Despite this result for the mechanical response, it is worth observing that improvement in the electrical conductivity of 93% makes the combination of PPY/GNP the best option for a more effective current collector in TENG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 for a schematic view of the device), an S-TENG is assembled with a modified textile prepared from the deposition of polypyrrole on textile in contact with a layer of Ecoflex. 85 Independent triboelectric layer mode (I mode)…”
Section: Single Electrode Mode (Se Mode)mentioning
confidence: 99%